2015
DOI: 10.1158/1538-7445.am2015-4327
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4327: Nek6 and Hif-1α cooperate with the cytoskeletal gateway of drug resistance to drive outcome in serous ovarian cancer

Abstract: Hypoxia selects the most aggressive and drug-resistant clones in solid malignancies. One of the pivotal transcription factors induced by hypoxia is Hif-1α. However, in serous ovarian cancer (SEOC), Hif-1α expression is not a prognostic biomarker. This study aims to assess the hypothesis that the serine-threonine kinase Nek6 functions as a downstream effector cooperating with Hif-1α in driving ovarian cancer aggressiveness. Nek6 was overexpressed and Hif-1α was silenced in A2780 cells. Nek6 was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Although this is not an unusual finding, since synergism and antagonism can be different at different dose levels 47 , it certainly requirer further investigation to properly identify the best combination drug schedule. Results from the combination studies are in line with our previous findings demonstrating that stable NEK6 silencing in ovarian cancer cells produced a modest but significant increase of cisplatin and paclitaxel sensitivity, while a stable overexpression slightly increased drug resistance 11 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Although this is not an unusual finding, since synergism and antagonism can be different at different dose levels 47 , it certainly requirer further investigation to properly identify the best combination drug schedule. Results from the combination studies are in line with our previous findings demonstrating that stable NEK6 silencing in ovarian cancer cells produced a modest but significant increase of cisplatin and paclitaxel sensitivity, while a stable overexpression slightly increased drug resistance 11 .…”
Section: Resultssupporting
confidence: 89%
“…NEK6 is also directly phosphorylated by CHK1 and CHK2, thus being identified as a novel direct target of the DNA damage checkpoint 10 . Notably, overexpression of NEK6 has been linked to many human diseases including liver, breast, lung, stomach, colon, larynx, ovary and prostate cancer 11 16 , and in line with these findings, we also recently showed that NEK6 is an independent unfavorable prognostic marker in ovarian cancer 11 . Taken together these data indicate that although the precise role in tumorigenesis remains unknown, NEK6 actually represents an attractive target for new anticancer therapies and inhibitors of NEK6 could be powerful compounds in the clinical setting.…”
Section: Introductionsupporting
confidence: 83%
“…A bioinformatic analysis showed the presence of HRE (Hypoxia Responsive Elements) motifs in 5 and 3 UTR of the NEK6 gene, which may be important for NEK6 regulation by HIF-1α. Additionally, in two groups of patients, concomitant expression of HIF1A and NEK6 was detected [147]. These data show that NEK6 can be regulated by HIF-1α in hypoxic conditions in serous epithelial ovarian cancer and may also be related to resistance to chemotherapeutic treatment.…”
Section: Nek6mentioning
confidence: 56%
“…In recent years, altered expression and activity of NEK6 were associated with several types of cancer, such as liver [139], prostate [140], gastric [141][142][143], colorectal [144,145], breast [146], serous epithelial ovarian [147], thyroid [148], and retinoblastoma cancers [149]. In addition, inflammation-based diseases, such as ulcerative colitis, have also been linked to NEK6 [28].…”
Section: Nek6mentioning
confidence: 99%
See 1 more Smart Citation